Legal Protection Based On The Principle Of Proportion: Maintaining A Balance Of Debtor And Creditor Rights In The Execution Of Fiduciary Guarantees - Simbolon, Tota Prima; Sidauruk, Jinner (Inspiring Law Journal, 2025)
Creditors cannot execute fiduciary guarantees independently; instead, they must file an execution request with the court until a legally binding decision is made. There is no agreement in this decision regarding the debtor's breach of contract and the debtor's willingness to surrender the fiduciary guarantee. The results of this study are as follows: there are no standards regarding the requirements that must be met in the execution auction application documents; many standards regarding execution titles equivalent to court decisions that have permanent legal force; no special category for execution auctions; fiduciary guarantees no longer pay special attention to the ease of execution; and agreement clauses mentioning the debtor's breach of promise and willingness to surrender have non-legal consequences, such as: a surge in execution applications in court; difficulty obtaining credit if the object of the fiduciary guarantee is executed; and the lengthy court execution process, which requires time and costs that can affect the trust in legal protection policies based on the principle of proportionality between the giver and receiver of the fiduciary guarantee